She-wolves: England's early queens. Episodes 1-3 [videorecording (DVD)] - Castor, Helen; Swingler, Lucy (Acorn Media, 2013)
Hosted and based on the book by Dr. Helen Castor, and filmed on location in England and France, this BBC series explores the lives of seven English queens who challenged male power, the fierce and fiery reactions they provoked, and whether, in fact, much has changed.